First simultaneous evaluation of fission probabilities and neutron-induced cross sections for the Pu fissile isotopes - Bouland, Olivier; Marini, Paola (Nuclear data sheets, 2024)
Surrogate reactions are a powerful tool to access neutron-induced reaction cross sections of short-lived nuclei. However, to infer neutron-induced reaction cross sections from measured deexcitation probabilities requires a consistent and rigorous theoretical framework describing both charged-particle and neutron-induced reactions. This work presents the first practical application of the new approach developed in O. Bouland, Phys. Rev. C 100, 064611 (2019) to Pu fissile isotopes, 237,238,240,242,244Pu*. Average neutron-induced reaction cross sections and deexcitation probabilities measured in surrogate reactions are simultaneously analyzed with an efficient Monte Carlo R-matrix-extended theory algorithm using a unique set of nuclear-structure parameters to describe both observables. Fission probabilities allow one to estimate fission-barrier heights, not otherwise accessible in fissile isotopes. The theoretical framework is here extended to model 'giant' resonance structures observed in the fission probabilities of some nuclides. A careful study of the impact of the uncertainties on nuclear parameters and on the populated compound system angular distribution has been carried out. This study raises questions on the normalization of some fission probabilities measured in the 70's in (t,p) reactions, that could not have been pointed out without the use of the here-presented complex technique. This finding is especially important for the peculiar 240Pu* system. In addition, our study reveals for the 237Pu* compound system a 10 to 30% too high value of the only-performed low-energy neutron-induced fission cross section measurement (Gerasimov et al., JINR-E–3-97-213 (1997)) and, subsequently of the evaluated fission cross section below 50 keV for the 236Pu.